Islamic Learning Based on Digital Platforms - Nariswari, Safira Widiana; Azani, Mohammad Zakki (Universitas Muhammadiyah Surakarta, 2024)
This research explains the content of Islamic learning by utilizing technology through digital platforms. Focusing on YouTube which plays an important role as a means of da'wah media for popular preachers in Indonesia, with the aim of facilitating Muslims in accordance with the demands of the Quran and Hadith, speakers are also easy to convey da'wah in purifying Islam and returning to teachings sourced from the Quran, sunnah, and hadith of the Prophet Muhammad . The method used is qualitative, which is descriptive by describing the study of Islamic purification da'wah from the speaker on YouTube. Analysis of da'wah content is carried out to identify forms of Islamic purification in purifying Islamic teachings in accordance with demands. The result of this research is that today many people still follow traditions that are not in accordance with the teachings, therefore Islamic learning through digital platforms is expected to be able to help Muslims in purifying Islamic teachings and introducing Islam deeply in accordance with the teachings brought by the Prophet Muhammad, delivered by lecturers through YouTube media. The conclusion of the preachers in purifying the teachings of Islam is to purify the Tauhid of a Muslim in purifying the teachings of Islam is to strengthen the Akidah, strengthen Islam, improve morals.